The Psychological Condition of Major Character with Deaf Family in Movie Coda (2021) - Al Ghozali, Fikri Ali; Widiyanti, Ana (Metaphor, 2024)
This study aims to analyze how the deaf family affects the psychological of the major character in Coda (2021) and the major character's struggle to overcome her psychological condition in Coda (2021). The study uses a descriptive qualitative method to analyze the film entitled Coda, directed by Sian Heder and produced by Fabrice Gianfermi, Philippe Rousselet, Jerôme Seydoux, and Patrick Wachsberger in 2021 as the objective research. The collecting data of the research method includes watching and reading, identifying, and selecting. The data of the research method is displayed, analyzed, and explained. The researcher analyzes the data by using Sigmund Freud's theory of Psychoanalysis to analyze the data by displaying, explaining, and interpreting it. The result of the study are the representation of the deaf family's influence on the major character's psychology in the movie Coda (2021), the deaf family's influence on Ruby's psychology includes components such as id, ego, and super-ego. In addition, this study identifies various forms of anxiety and ego defense mechanisms experienced by Ruby; and the major character struggles to overcome her psychological condition. This study includes the major character's way of dealing with her psychological problems.